Why is Synedra berolinensis so hard to classify? More on monotypic taxa - Williams, David M. (Phytotaxa, 2013)
The diatom species Synedra berolinensis has been placed in the genus Synedra, Fragilaria, Staurosira, Staurosirella as well as its own monotypic genus, Belanostrum. It is recently returned to Staurosirella. This prompts a pertinent question: Why is Synedra berolinensis so hard to classify? One answer may be the inappropriateness of the evidence (data). Another may be the approach to classifying the organism, especially the use of monotypic taxa for problematic groups. I will address both aspects, concentrating more on the latter: How do we classify?